Novel Metal@Carbon Spheres Core–Shell Arrays by Controlled Self‐Assembly of Carbon Nanospheres: A Stable and Flexible Supercapacitor Electrode. Issue 6 (25th November 2014) - Xia, Xinhui; Zhang, Yongqi; Fan, Zhanxi; Chao, Dongliang; Xiong, Qinqin; Tu, Jiangping; Zhang, Hua; Fan, Hong Jin
<x xml:space="preserve">Abstract</x> The high performance of electrochemical energy‐storage devices relies largely on scrupulous design of nanoarchitectures and smart hybridization of bespoke active materials. Carbon nanopsheres (CNSs) are widely used for energy storage and conversion devices. Here, the directional assembly of CNSs on a vertical‐standing metal scaffold into a core/shell array structure is reported. The method uses a three‐step all‐solution synthesis strategy (chemical bath deposition, electrodeposition, and hydrothermal) and begins from ZnO microrod arrays as a sacrificial template. The self‐assembly of CNSs can be correlated to a simultaneous etching effect to the ZnO accompanying the polymerization of glucose precursor. The Ni microtube/CNSs arrays are selected as an example for structural and electrochemical characterizations. The novel type of metal/CNSs arrays is demonstrated to be a highly stable electrode for supercapacitors. The electrodes of metal/CNSs arrays are assembled into symmetric supercapacitors and exhibit high capacitances of 227 F g−1 (at 2.5 A g−1) and an outstanding cycling stability with capacitance retention of 97% after 40 000 cycles.